Cover Feature: Rhodium‐Catalyzed Enantioselective Synthesis of Highly Fluorescent and CPL‐Active Dispiroindeno[2, 1‐c]fluorenes (Chem. Eur. J. 44/2021). Issue 44 (12th July 2021) - Cadart, Timothée; Nečas, David; Kaiser, Reinhard P.; Favereau, Ludovic; Císařová, Ivana; Gyepes, Róbert; Hodačová, Jana; Kalíková, Květa; Bednárová, Lucie; Crassous, Jeanne; Kotora, Martin
Abstract : Helicenes are intriguing and inherently chiral compounds with fascinating 3D architecture. Their shape could be compared to whirlpools in the Naruto Strait as it is beautifully depicted in the famous woodcut by Hiroshige. Formation of the whirlpools requires special conditions and these are also required in helical compounds' syntheses. Synthesis of chiral fluorescent [7]helical indenofluorenes by using catalytic enantioselective [2+2+2]cyclotrimerization and their photophysical properties are reported. More information can be found in the Communication by D. Nečas, M. Kotora, et al. (DOI: 10.1002/chem.202100759 ).